Conflict of female sex workers in films Moammar Emka’s Jakarta Undercover - Daniel Susilo; Olinne Citra Rhamadany; Farida Farida; Irmia Fitriyah (Fakultas Ilmu Sosial UIN Sumatera Utara Medan, 2021)
AbstractMoammar Emka’s Jakarta Undercover is a movie that was lifted from four series of works by Moammar Emka with the same little. Moammar Emka’s Jakarta Undercover tells the Jakarta city nightlife that is full of surprises, which includes the ambitions of its citizens, various forms of prostitution and parties that claimed to be unknow, to drugs. This film has a mission voice humanity’s value to society. The director, dawn nugros wants to visualize and raise the issue of violence against women, thuggery, poverty, the screams of minorities. The purpose of this research is to find out the conflicts that occur in women of high sex workers. This research is a qualitative research using John Fiske semiotic analysis through The Televison Codes. The results of this study indicate that The Moammar Emka’s Jakarta Undercover movie, represents upper-class commercial sex workers as well some conflicts received by women. And shows the dark side of the Jakarta City, which is carried out by supermodels, officials, and other uppers classes. In addition, this study shows that some of the conflict underlying women work in the world of high class prostitution and invite many risks. That movie also gives a voice to women about gender inequality.